Elderly Class (Yoga, Acupressure and Progressive Muscle Reflexology) to Improve Elderly Health in Tambakmulyo Village, Puring, Kebumen - Kusumastuti, Kusumastuti; Muthoharoh, Siti; Rahmadhani, Wulan (Universitas Muhammadiyah Surakarta, 2024)
Elderly is someone who has entered the age of 60 years and above. The elderly are an age group in humans who have entered the final stage of their life phase. The increase in the number of elderly people has an impact, among others, the emergence of degenerative disease problems that often accompany chronic and multipathological elderly people such as hypertension, heart disease, diabetes mellitus, uterine / prostate cancer, osteoporosis and others, where the handling takes a long time and costs a lot. Elderly classes for elderly health are expected to foster the ability of the elderly themselves to overcome health problems with the support and guidance of professionals, towards the realization of a healthy elderly life. The design of activities to achieve goals is planning (planning), implementation (action), evaluation (evaluation) and follow-up (follow up). In detail the methods and mechanisms. The results of the activity refer to the predetermined target outcomes, namely that the elderly can take part in elderly classes and can increase the elderly's knowledge about Yoga, Acupressure, and Progressive Muscle Reflexology. Yoga, acupressure, and ROP training will increase the knowledge of the elderly, so that it will also affect the accuracy of yoga, acupressure, and ROP training. By getting training, it is hoped that the elderly can understand and be skilled in applying yoga, acupressure, and ROP.